PERAN ORANG TUA SISWA DAN GURU DALAM PELAKSANAAN PROGRAM TNP2K DAERAH 3T - Damianus, Damianus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Education is a very important tip of the pandemic in this country, where there are still many educational inequalities in areas that are far from perfect, especially in the interior of West Kalimantan which islocated in Landak Regency, Sebangki District. In this area, education is very lagging behind and is included in the 3T zone area (Terdepan, Terpencil and Terluar). The purpose of this study is to see the results and images of students during the implementation of the TNP2K KIAT Guru program in areas that are included in the 3T zone category, namely SDN 08 Kumpang Tengah. In this study, the author used a descriptive analysis method with a qualitative approach. Data collector used is interview, observation, and documentation. This type of research is a case study by analyzing the results of the program being carried outan. Researcher participants totaled 20 people. Data analysis techniques include data collection, data presentation, conclusion drawing and verification. Based on the results of the study, the implementation of the TNP2K KIAT program for 3T regional teachers at SDN 08 Kumpang Tengah, Sebangki District, Landak Regency in 2022. (1) One of the follow-up activities of the KIAT Guru Policy Pilot Program which aims to improve the quality and services of education from the Ministry of Education, Culture, Research and Technology in collaboration with TNP2K (National Team for the Acceleration of Poverty Reduction) (2) Budget reporting of activities is very clear and transparent, parents and the community around SDN 08 Kumpang Tengah can monitor and know every use of the budget managed by the School. There are a lot of extracurricular activities of students (3) every month the parents of the students are required to have a meeting, this has become a rule and mutual agreement in accordance with the TNP2K program plan for the 3T area. (4) Reporting of student activities from parents and re-transported by the school to be a report of each activity that will later be sent to District and central education offices.